Diversity and Effectiveness of Insect Pollinators of Jatropha curcas L. (Euphorbiaceae) - Puji Rianti; Bambang Suryobroto; Tri Atmowidi (HAYATI Journal of Biosciences, 2010)
Seed of Jatropha curcas (Euphorbiaceae) is currently established as the source for biofuel Therefore, it is important to understand the diversity insects that pollinated J. curcas inflorescence yellow flowers. We also aimed to study the pollination effects on fruit set on J. curcas. Scan sampling method were carried out to explore the insect pollinators diversity from 07.00 up to 17.00 h  in every 15 minutes. Visiting frequency of pollinators insects were observed by using focal sampling. Those information together with flowering periods, flower nectar volumes, and environmental factors were used as the basic data to determine the effectiveness of insect pollination both in covered and uncovered of seed set plants. Results showed that nine species of insect pollinators were from three order (Hymenoptera, Lepidotera, and Diptera) pollinated J. curcas. Four species of Hymenoptera i.e. Prenolepis, Apis dorsata, Xylocopa confusa, and Apis cerana showed  the highest abundances. The highest abundance and species richness of pollinators occurred at 08.00-10.15 and 15.00-17.15 h. Bees of X. confusa, A. cerana, and A. dorsata of Apidae are effective as insect pollinators in J. curcas plantations, due to high visited frequencies. The insect pollinators also increased fruits and seeds set of J. curcas in the uncovered experiment plants. Thereby, enhancement the three pollinator insects as part of crop management have to be considered by farmers.